2018
DOI: 10.3389/fpsyg.2018.00920
|View full text |Cite
|
Sign up to set email alerts
|

Future and Present Hedonistic Time Perspectives and the Propensity to Take Investment Risks: The Interplay Between Induced and Chronic Time Perspectives

Abstract: Willingness to take risk is one of the most important aspects of personal financial decisions, especially those regarding investments. Recent studies show that one’s perception of time, specifically the individual level of Present Hedonistic and Future Time Perspectives (TPs), influence risky financial choices. This was demonstrated for both, Time Perspective treated as an individual trait and for experimentally induced Time Perspectives. However, on occasion, people might find themselves under the joint influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…As aggregation helps in the decision-making process and enhances the operational and FE of a firm. The same results are backed up by the research work (Sekścińska et al, 2018). The third hypothesis was proposed, the results of this study have accepted this hypothesis, and the same idea has been backed up by a survey (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…As aggregation helps in the decision-making process and enhances the operational and FE of a firm. The same results are backed up by the research work (Sekścińska et al, 2018). The third hypothesis was proposed, the results of this study have accepted this hypothesis, and the same idea has been backed up by a survey (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…Increasingly high levels of power measured with the Sense of Power Scale [ 34 ] have been shown to be associated with the creation of riskier portfolios and more risky choices in the context of gambling. Similarly, a situationally induced high-power condition has been shown to result in greater investment and gambling risks than a low power condition [ 35 ]. However, these are the only studies on power and individual risky financial decisions, as far as we are aware; therefore, further studies that replicate and extend the effect are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, taking into consideration the scarcity of studies demonstrating the impact of power on risky financial decisions and the value of replication, we aimed to verify previous findings that power enhances willingness to take risks when making investment decisions [ 35 ]. Therefore, we hypothesized that:…”
Section: Introductionmentioning
confidence: 99%
“…Plus, there is no guarantee the experiential learning from employment will have a significant future payoff. Numerous studies have confirmed that FTP is linked to the propensity to take risks (Zimbardo et al, 1997;Keough et al, 1999;Henson et al, 2006;Sékscińska, Rudzinska-Wojciechowska, & Maison, 2018). These Research Journal, 11(4):925-938, 2020 An Eye Toward the Future: Examining the Relationship Between Future Time Perspective and College Student Employment in the United States findings imply a positive relationship between FTP and college student employment.…”
Section: Ftp and College Student Employmentmentioning
confidence: 99%